Uma análise reflexiva sobre o uso de agrotóxicos: um estudo de caso dos sujeitos sociais da feira de Chapecó, SC - Bohner, Tanny Oliveira Lima (2019)
This doctoral thesis aims to analyze how family farmers, consumers and professionals of agronomic field involved in the conception or operation of the free fair from Chapecó perceive the use of agrochemicals in agricultural production, particularly with regard to their understanding of the risks to which they are ex- posed, as well as the establishment of a reflexive response to this condition. The theoretical contribution that underlies the present study is based on sociological analyzes proposed by Ulrich Beck and Niklas Luhmann, concerning risks and dangers of late modernity, especially with regard to the implications of new technologies, to which social subjects are exposed by various means, including food production and con- sumption. In this context, this qualitative study was developed through a case study, carried out in the mu- nicipality of Chapeco, SC. Secondary data were collected through bibliographical research, and primary data through semi-structured interviews. Results indicate that risk perception and reflexive response to- wards the risks differs among the groups of respondents. Conventional farmers showed a reduced percep- tivon towards the implications related to pesticide use, largely limited by the widespread of the concept of safe usage by industries, which hampers individual reflexion. This factor is aggravated by the preferences of consumers, which relies on visual patterns of the products, as well as by the lack of stimuli to develop a reflexive posture. On the other hand, agroecological farmers revealed to acknowledgethe risks associated with exposure to pesticides, manifesting a reflexive behavior, driven by the experience of a risk situation in their families and consolidated through the contestation of the dominant rationality. However, the products offered by these farmers are overlooked by most of the consuming public, which, in turn, express an incipi- ent reflexivity concerning the risks associated with consumption of conventional food. In this regard, inter- views with consumers who buy their food in the conventional sector revealed that, although the consumer does not have the intention to purchase a conventionally produced product, neither presents a reflexive conduct, as the need to purchase a product of agroecological origin is not a concern. Despite this general situation, a few respondents of this group reported purchasing conventional food due to the lack of diversity and availability of agroecological foods, or even for not acknowledging the mode of production. On the other hand, consumers who seek agroecological products manifest an elevated perception and response to these risks, expressed by the recognition of damage caused by food exposure to pesticides and the prioriti- zation of agroecological food. Likewise, to the rural extension agents who are or have already been in- volved with the organization of the fair, it is imperative to reform the current production system towards agroecological agriculture, a most appropriate way of conducting productive system, which environmental and economic viability are attested by their reports. Therefore, it is concluded that, in the referred context, it is necessary to raise awareness of the conventional farmers and consumers in general respecting the risks associated with the use of chemical inputs in food production in order to develop a reflexive conduct, thus encouraging new forms of production and consumption, which might enhance the quality of life of people involved.